Peran badan lingkungan hidup dalam pengelolaan lingkungan :: Studi tentang kerusakan lingkungan akibat penambangan pasir dan batu di Sungai Oba Kota Tidore Kepulauan - ADJAM, Syarifuddin ([Yogyakarta] : Universitas Gadjah Mada, 2010)
An environmental damage polluted by the activity of mining today is unavoidable anymore. The high need of human beings to build is one of the main factors of it. The role of the government becomes essential to preserve and minimize this polluted environment. This research aims to analyze the effectiveness of the environment institution (BLH) in Tidore City toward environmental preservation especially the case of sand and stone mining activity at Oba River. The method used here is field survey with field variables consisting of respondent’s understanding of the activity of mining, environmental damage (a biotic, biotic, culture), and the role of environment institution (supervision, co-ordination, and control). Data analysis used is based on frequency table and cross-tabulation. To understand the connection of all variables it uses product-moment correlation. The results of this research show that stakeholder’s knowledge about that is in the middle level, and the community group’s is in the low level. For the environmental damage, stakeholder group considers it in the middle category and for component-a biotic damage executive group considers it in the high category as well as for cultural environmental damage, private enterprise's group considers it in high. There are variant connections within the components of polluted environment; a biotic component has significant connection with biotic component, the component of a biotic environment has no significant connection to culture component, and biotic component has no significant connection with culture component. There is no significant connection of science to environmental damage even the implementation of the functions of environment institution (BLH). Generally speaking, stakeholder group said that environment institution (BLH) functions in the middle level while private enterprise's group assesses that the supervision is in the high level. For executive group, group coordination is in the high level and the control is for society’s group in the high level as well. There are significant connections in implementing the functions of environment institution (BLH) sin Tidore City.